Silicification, flow pathways, and deep-seated hypogene dissolution controlled by structural and stratigraphic variability in a carbonate-siliciclastic sequence (Brazil). (May 2022) - Pisani, Luca; Antonellini, Marco; Bezerra, Francisco H.R.; Carbone, Cristina; Auler, Augusto S.; Audra, Philippe; La Bruna, Vincenzo; Bertotti, Giovanni; Balsamo, Fabrizio; Pontes, Cayo C.C.; De Waele, Jo
Abstract: Fractured and karstified carbonate units are key exploration targets for the hydrocarbon industry as they represent important reservoirs. Furthermore, large water reserves and geothermal systems are hosted in carbonate aquifers. This paper documents the relationships between stratigraphy, structural patterns, silicification, and the spatial-morphological organization of a 3D multistorey cave system developed in a Neoproterozoic mixed carbonate-siliciclastic sequence. We found that the combination of lithology, silicification, fracture patterns (controlled by lithostratigraphic variability), and petrophysical properties control the formation of high or low permeability zones; their distribution was fundamental for the spatial organization of dissolution and the compartmentalization of the resulting conduit system in different speleogenetic storeys. We propose a deep-seated hydrothermal origin for the fluids involved in the main phases of karst formation. Warm and alkaline hydrothermal fluids caused silica dissolution, followed by chalcedony and quartz reprecipitation in pore space and fractures. Rising fluids concentrated along through-going vertical fracture zones in the lower storey, whereas sub-horizontal bedding-parallel fluid flow was focused on sedimentary packages containing highly silicified dolostones (SiO2 >80 wt%) characterized by high permeability. The Calixto Cave is an enlightening example for the complex speleogenetic history affecting a mixed carbonate-siliciclastic succession where the combined effect of silicification and hydrothermal karst dissolution can potentially generate high-quality reservoirs. Graphical abstract: Image 1 Highlights: Stratigraphy and structures interplay in forming high-vs. low-permeability units. High-permeability zones are focused in the silicified carbonates. Mineral deposits and silica dissolution suggest a hypogene hydrothermal origin for the conduit system. The 3D organization of the conduit system reflects the interplay among stratigraphy, fracture patterns and silicification.